CURRICULUM ANALYSIS OF MASTER PROGRAM IN ISLAMIC HIGHER EDUCATION - Muhammad Munadi; Rustam Ibrahim; Noor Alwiyah (Ta'dib, 2021)
The purpose of this research is to analyze the construction and content of the curriculum of Postgraduate, especially on Master Program in Islamic Religious Education at two Islamic Higher Education – private and public. The method used in this research is a descriptive qualitative method by focusing on curriculum construction and then analyzingit using content analysis.The results of this research show that the curriculum construction of the Master Program in Islamic Religious Education at UIN Maulana Malik Ibrahim and UNISMA Malang is based on the grouping of subjects according to the demands of the Indonesian National Qualification Framework at the 8 level. The curriculum content is mainly dominant in strengthening Pedagogical Content Knowledge (PCK). Second, Postgraduate does not provide alternative curriculum so there is no flexibility.  Curriculum of the master program in Islamic Religious Education must be able to strengthen the content knowledge of Islamic education.